Phosphotyrosine profiling of curcumin-induced signaling. Issue 1 (December 2016) - Sathe, Gajanan; Pinto, Sneha; Syed, Nazia; Nanjappa, Vishalakshi; Solanki, Hitendra; Renuse, Santosh; Chavan, Sandip; Khan, Aafaque; Patil, Arun; Nirujogi, Raja; Nair, Bipin; Mathur, Premendu; et al.
Abstract Background Curcumin, derived from the rhizomeCurcuma longa, is a natural anti-cancer agent and has been shown to inhibit proliferation and survival of tumor cells. Although the anti-cancer effects of curcumin are well established, detailed understanding of the signaling pathways altered by curcumin is still lacking. In this study, we carried out SILAC-based quantitative proteomic analysis of a HNSCC cell line (CAL 27) to investigate tyrosine signaling in response to curcumin. Results Using high resolution Orbitrap Fusion Tribrid Fourier transform mass spectrometer, we identified 627 phosphotyrosine sites mapping to 359 proteins. We observed alterations in the level of phosphorylation of 304 sites corresponding to 197 proteins upon curcumin treatment. We report here for the first time, curcumin-induced alterations in the phosphorylation of several kinases including TNK2, FRK, AXL, MAPK12 and phosphatases such as PTPN6, PTPRK, and INPPL1 among others. Pathway analysis revealed that the proteins differentially phosphorylated in response to curcumin are known to be involved in focal adhesion kinase signaling and actin cytoskeleton reorganization. Conclusions The study indicates that curcumin may regulate cellular processes such as proliferation and migration through perturbation of the focal adhesion kinase pathway. This is the first quantitative phosphoproteomics-based study demonstrating the signaling events that are altered in response to curcumin. Considering the importance of curcumin as an anti-cancer agent, this study will significantly improve the current knowledge of curcumin-mediated signaling in cancer.